Out-of-home care experience and juvenile delinquency during transition from adolescent to adult - Li, Yang (2011)
The transition of youth from adolescence to adulthood is usually a difficult and painful period. This is an even more difficult time for the youth who are removed from the home of biological parents to be placed into out-of-home care. For them, they not only had the experience of maltreatment, hurt or neglected, but also are facing the uncertainties associated with being removed from the original family. Under this situation, their behavior development may be troublesome, as they may desire returning to the original home, or conflict with foster parents and siblings. As a result, such children may join a delinquency group for support. If the experience of out-of-home care affects youth behavior negatively and can promote delinquency, then out-of-home care is at least the second great tragedy in a difficult upbringing. There is a great risk for delinquent or crime behavior among those who experience physical abuse, rejection or neglect from parents. Every year, federal, state and local governments spend tremendous sums on child welfare to protect children from maltreatment and abuse. However, how youth experience out-of-home care and whether out-of-home care effectively reduces the risk for delinquency among those who are in placement should be a noteworthy question for examination. Studies reveal several relationships between out-of-home care experience and youth delinquency. For example, there is a positive correlation between number of placements and increased delinquency levels (Runyan & Gould, 1985; Ryan & Testa, 2005; Widom C. S, 1991). As for more detailed study, only a few studies examine the delinquent behavior difference among different placements. For example, about a quarter of the youths in out-of-home care responded with delinquency, and the most commonly reported delinquency were less serious offenses (Courtney, Piliavin, Grogan-Kaylor, & Nesmith, 2001). Children who entered kinship care have a lower estimated risk of behavioral problems than children who entered foster care, and children who moved from foster care to kinship care also showed less behavioral problems (Rubin, Downes, O'Reilly, Mekonnen, Luan, & Localio, 2008). Although these findings demonstrate variation, no study carefully examines whether the relationship between the experience in out-of-home care youth and caregiver affects juvenile delinquent behaviors. Out-of-home care programs in the United States are mainly categorized with foster care, kinship care, group care, independent living and other placements. Maltreated youth are selected into certain placement by their own situations and court placements. To further investigate out-of-home care youth delinquency and life experience, the focus of the current study is how different types of placement affect juvenile delinquency, and investigate whether different out-of-home care experiences predict juvenile delinquency seriousness. This study explores the relationships between youth delinquency and different out-of-home care experiences from the age of 17-22. The first research question is to compare different delinquent or criminal behavior levels when youth were placed in different types of out-of-home care. This question aims to find out specific delinquency frequencies and general out-of-home care youth delinquency patterns. The second research question is to test whether out-of-home care experience affect later delinquent behaviors. And the third question is to examine whether different life circumstance predict non-violent and violent offending. Although they are exposed to a higher risk of conducting delinquency or crime due to early maltreatment experiences, they also are under the protection from out-of-home care service in the child welfare system. Some youth experience out-of-home care negatively and this increases delinquency relatively. Early entry into foster care also predicts more serious delinquency. But also, some positive outcomes and these experience prevent youth from delinquent behaviors, such youth tend to be placed in foster care and kinship care, and to have good relationships with caregivers. The precise mechanisms and characteristics of who does well after placement remain unknown for the present. Hopefully, the findings of this study can have several implications for future policy making and academic research